Walter Dyk: Son of Old Man Hat: A Navajo Autobiography - Guédon, Marie-Françoise (Matrix)

(untitled) (International Network for Training, Education, and Research on Culture, 2025)
Marie-Françoise Guédon reviews Walter Dyk's 1938 classic ethnographic recording, Son of Old Man Hat: A Navajo Autobiography.